Planar block adjustment and orthorectification of Chinese spaceborne SAR YG-5 imagery based on RPC. Issue 3 (1st February 2018) - Wang, Taoyang; Zhang, Guo; Li, Deren; Zhao, Ruishan; Deng, Mingjun; Zhu, Tong; Yu, Lei
ABSTRACT: Yaogan-5(YG-5), launched in December 2008, is a Chinese high-resolution spaceborne synthetic aperture radar (SAR) satellite, with a ground resolution of 3 m. However, the direct geometric positioning accuracy of YG-5 slant range images is low and so is the mosaic accuracy of the orthoimages. To improve the geometric accuracy of YG-5 orthoimages, this article proposes a strategy to calculate the rational polynomial coefficients for each SAR image and then uses a planar block adjustment method to solve for the orientation research parameters of the SAR images to achieve the orthorectification while a auxiliary digital elevation model is necessary for height constraint. Compared with the traditional orthorectification method using a single image, this strategy can ensure both uniformity in positioning accuracy of orthorectified images and high mosaic accuracy of adjacent orthoimages based on a small number of ground control points (GCPs). Tests using Chinese YG-5 satellite data over Xi'an and Xianning, China show that, using four GCPs positioned in the four corners of the test area, we can achieve independent check point plane accuracies better than ±4 m after the planar block adjustment. Finally, this article demonstrated that seamless mosaic geometry levels can be attained after the block orthorectification.